2020
DOI: 10.1038/s41598-020-73032-0
|View full text |Cite
|
Sign up to set email alerts
|

Full-field flicker evoked changes in parafoveal retinal blood flow

Abstract: When retinal activity is increased by exposure to dynamic visual stimuli, blood vessels dilate and the flow of blood within vessels increases to meet the oxygen and glucose demands of the neurons. This relationship is termed ‘neurovascular coupling’ and it is critical for regulating control of the human retinal vasculature. In this study, we used a recently developed technique based on a dual-beam adaptive optics scanning laser ophthalmoscope to measure changes in red blood cell velocities, vessel diameter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
8
2
1
Order By: Relevance
“…For arterioles and venules, when measuring RBC velocity responses to flicker stimulation, we have shown that individual capillary RBC velocities vary across capillaries (either increasing or decreasing), differing from arterioles and venules, which show a consistent response. 10 , 24 , 41 Unlike other studies that have found increases in RBC velocity in larger retinal vessels during flicker stimulation, 42 44 our capillary measurements in this study showed an increase in RBC velocity in only three out of the five subjects, although from a larger sample we found on average that capillary flow increased by about the same amount as arteriole flow, but the change was not statistically significant, in part due to the variability in capillary measurements. 24 …”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…For arterioles and venules, when measuring RBC velocity responses to flicker stimulation, we have shown that individual capillary RBC velocities vary across capillaries (either increasing or decreasing), differing from arterioles and venules, which show a consistent response. 10 , 24 , 41 Unlike other studies that have found increases in RBC velocity in larger retinal vessels during flicker stimulation, 42 44 our capillary measurements in this study showed an increase in RBC velocity in only three out of the five subjects, although from a larger sample we found on average that capillary flow increased by about the same amount as arteriole flow, but the change was not statistically significant, in part due to the variability in capillary measurements. 24 …”
Section: Discussioncontrasting
confidence: 91%
“…The sizes of the variations in RBC velocity were consistent with the results of Experiment 1. Even though flicker stimulation has been shown to cause an overall increase in capillary blood velocity of about 15%, 24 the larger ongoing variability of 17% to 20% in the individual capillaries is consistent with some increasing blood velocity and others decreasing during the flicker stimulation.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations